KARAKTERISTIK MINUMAN WHEY YANG DIFERMENTASIKAN DENGAN BAKTERI ASAM LAKTAT INDIGENUS ASAL DANGKE - Setiawan Putra Syah; Irma Isnafia Arief; Epi Taufik; Cece Sumantri (Jurnal Teknologi dan Industri Pangan, 2017)
Whey from the dangke processing center in Enrekang district, South Sulawesi, is the main by-product which can contribute to environmental pollution. On the other hand, the nutritional content of whey is highly potential to be developed into high value food products and provide functional benefits. Whey processing into a fermented drink is one of the easy and inexpensive alternatives with good prospect to be developed. The aim of this study was to investigate the microbial, physical, chemical and sensory characteristics of the whey drink fermented (FWD) by probiotic lactic acid bacteria (LAB) isolated from dangke. The LAB strain used were Lactobacillus fermentum strains B323K, C113L, A323L, C222L, and B111K. The results showed that the LAB strains grew well the whey medium and the viability met the standard of dairy fermented product. FWD have similar pH, % titratable acidity, and aW characteristics in all fermentation treatments with LAB strains from dangke, however to adjust the pH and acidity level of FWD to the yoghurt standard (pH 4.4 and %TAT 0.9–1.2%), the FWD fermentation must be stopped at the 20th hour. Changes in the level of moisture, ash, and carbohydrate contents of FWD occurred after the fermentation. The sensory quality tests showed that the FWD fermented by LAB strains from dangke was preferred by the panelists than the unfermented one (Whey + 8% sucrose).